Morphological and Thermal Properties of Composites Prepared with Poly(lactic acid), Poly(ethylene-alt-maleic anhydride), and Biochar from Microwave-pyrolyzed Jatropha Seeds - Khui, PLN.; Rahman, R.; Ahmed, A. S.; Kuok, K. K.; Bin Bakri, M.K.; Tazeddinova, D.; Kazhmukanbetkyzy, Z. A.; Torebek, B. (My University, 2021)
The morphological and thermal properties of composites containing a bioplastic blend and micro/nano-sized biochar from pyrolyzed jatropha seeds from microwave pyrolyzed jatropha seeds were investigated using scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, and differential scanning calorimetry. The biocomposite samples exhibited a brittle structure with a slightly ductile chip-like appearance. The Fourier transform infrared spectroscopy results for the PLA/PEMA/BC bio-composites were comparable to the PLA/BC biocomposites. A lower bio-filler content had more pronounced peak intensities than the higher bio-filler content biocomposites. The added PEMA compatibilizer in the PLA/PEMA/BC biocomposite showed more pronounced peaks, which indicated slightly improved bonding/interaction between the bio-filler and the matrix. Overall, increasing bio-filler content did not drastically affect the functional groups of the biocomposites. Thermogravimetric and differential scanning calorimetry analysis showed the developed biocomposites had a slight improvement in thermal stability, in comparison to the PLA sample. Improvements in the thermal stability of the PLA/PEMA/BC biocomposite could be attributed to the additional hydroxyl group, which was due to the added PEMA in the PLA and PLA/BC. According to the results of the analysis of the developed biocomposites, the biocomposites were more brittle and had reasonable thermal stability.Морфологические и термические свойства композитов, содержащих смесь биопластов и микро / наноразмерный биоуголь из пиролизованных семян ятрофы из микроволновых пиролизованных семян ятрофы, были исследованы с помощью сканирующей электронной микроскопии, инфракрасной спектроскопии с преобразованием Фурье, термогравиметрического анализа и дифференциальной сканирующей калориметрии. Образцы биокомпозита имели хрупкую структуру со слегка пластичным стружкообразным видом. Результаты инфракрасной спектроскопии с преобразованием Фурье для биокомпозитов PLA / PEMA / BC были сопоставимы с биокомпозитами PLA / BC. Более низкое содержание бионаполнителя имело более выраженные пиковые интенсивности, чем биокомпозиты с более высоким содержанием бионаполнителя. Добавленный агент совместимости PEMA в биокомпозит PLA / PEMA / BC показал более выраженные пики, которые указали на несколько улучшенное связывание / взаимодействие между бионаполнителем и матрицей. В целом увеличение содержания бионаполнителя не оказало существенного влияния на функциональные группы биокомпозитов. Термогравиметрический и дифференциальный сканирующий калориметрический анализ показал, что разработанные биокомпозиты имели небольшое улучшение термической стабильности по сравнению с образцом PLA. Повышение термической стабильности биокомпозита PLA / PEMA / BC можно объяснить дополнительной гидроксильной группой, которая была обусловлена добавлением PEMA в PLA и PLA / BC. По результатам анализа разработанных биокомпозитов биокомпозиты были более хрупкими и обладали приемлемой термической стабильностью.
BIORESOURCES. - 2021.
Keywords: импакт-фактор 2021; web of science; кларивате аналитикс; зарубежные авторы; томсон; зарубежное издание; научный журнал; дальнее зарубежье; биопластика; бионаполнители; биокомпозиты